Seroprevalence and related risk factors of Brucella spp. in livestock and humans in Garbatula subcounty, Isiolo county, Kenya - Mwatondo, Athman; Muturi, Mathew; Akoko, James M.; Nyamota, Richard; Nthiwa, D.; Maina, J.; Omolo, J.; Gichuhi, S.; Mureithi, M.W.; Bett, Bernard K. (2023)
Background Brucellosis is a neglected zoonotic disease that affects both animals and humans, causing debilitating illness in humans and socio-economic losses in livestock-keeping households globally. The disease is endemic in many developing countries, including Kenya, but measures to prevent and control the disease are often inadequate among high-risk populations. This study aimed to investigate the human and livestock seroprevalence of brucellosis and associated risk factors of Brucella spp. in a pastoralist region of northern Kenya.